2015
DOI: 10.3109/02699052.2015.1004748
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and executive dysfunctions following orbito-basal lesions in traumatic brain injury

Abstract: These findings add information regarding acute olfactory status following TBI and provide evidence on the importance of assessing olfaction very early post-TBI in order to plan intervention and determine what accident prevention advice will be required for home or work re-integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…When we focused on the thalamus as a seed, we found that several frontal lobe regions (the OFL and SFG) appeared to have disrupted connectivity with the thalamus in SVCI. The relationship between the OFL and executive dysfunction has been well established and is supported by the fact that the patients with orbito-basal lesions in traumatic brain injury always exhibit executive dysfunction (de Guise et al, 2015 ). Additionally, the OFL is one of the origins of frontal-subcortical circuits and has reciprocal connections with the thalamus, which provides the direct structural basis for functional connectivity (Bonelli and Cummings, 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…When we focused on the thalamus as a seed, we found that several frontal lobe regions (the OFL and SFG) appeared to have disrupted connectivity with the thalamus in SVCI. The relationship between the OFL and executive dysfunction has been well established and is supported by the fact that the patients with orbito-basal lesions in traumatic brain injury always exhibit executive dysfunction (de Guise et al, 2015 ). Additionally, the OFL is one of the origins of frontal-subcortical circuits and has reciprocal connections with the thalamus, which provides the direct structural basis for functional connectivity (Bonelli and Cummings, 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, patients with posttraumatic OD may also be unaware of their olfactory impairment, possibly due to cognitive dysfunction, hence generalizations for different etiologies based on the acuity of OD must be made very cautiously (43,44) . Our results are nevertheless necessary to serve as motivation for pursuing such longitudinal study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] A single mTBI is associated with impaired olfaction that may involve contortion of the olfactory nerve and/or direct injury to the olfactory system (e.g., olfactory bulb in the ventral part of the frontal lobe or olfactory cortex structures, such as the frontal lobe base or MTL). 17,[19][20][21][22][23]26,27,29,79,80 In particular, in TBI (including mild), traumatic lesions in the frontal lobe in general, and the basal frontal lobe in particular, result in lower odor identification test scores relative to lesions anywhere else in the brain. 21,[79][80][81] The longitudinal effects of a single mTBI/concussion on olfaction are unclear because of the lack of prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…17,[19][20][21][22][23]26,27,29,79,80 In particular, in TBI (including mild), traumatic lesions in the frontal lobe in general, and the basal frontal lobe in particular, result in lower odor identification test scores relative to lesions anywhere else in the brain. 21,[79][80][81] The longitudinal effects of a single mTBI/concussion on olfaction are unclear because of the lack of prospective studies. However, it is noted that most head impacts in football occur at the front of the head 82 and RHI can lead to long-term structural and functional brain changes to olfactory structures, including the OFC, anterior corpus callosum, and MTL, and former NFL players have been shown to exhibit fMRI activation impairment of the frontal lobe, as well as hippocampal atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation